Efektifitas Perawatan Metode Kanguru Intermitten Dalam Peningkatan Berat Badan Bayi Berat Lahir Rendah di RSUD Tugurejo Semarang Tahun 2013 - Heraswati Heraswati; Sri Rahayu; Nur Khafidhoh (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
Incidence of low birth weight babies (LBW) Regional General Hospital Tugurejo Semarang (Hospital) in 2012 as many as 212 LBW infants, babies with low birth weight is where there are treated with care incubator. Incubator care is very expensive and separating the baby from his mother. Intermittent kangaroo care method is one way of taking care of babies with low birth weight infants who underwent treatment for kangaroo method intermittent breathing frequency, body temperature, and oxygen saturation better, it can make the baby comfortable and quiet so that calories can be obtained to improve LBW weight, compared with infants who did not do kangaroo care method intermittent. This study to know the difference changes the baby's weight low birth weight (LBW) conducted kangaroo care method performed intermittently with incubator care. This research is quantitative research design used was a pre-experimental (pre Experiment) research that classifies members of the sample in the experi- mental group (treatment) and the control group. Population of this study is all LBW infants were born and cared for in hospitals Tugurejo is 20 infant, samples were taken of LBW infants who met the inclusion criteria is 14 infant. Using acci- dental sampling technique. Data collection by measuring the weight loss was lbw after. The results mean weight gain of LBW performed intermittent kangaroo care method that is 2.7 grams, the average weight gain of LBW who do care incu- bator at 3.1 grams. So that there was no difference in weight change LBW infants who do kangaroo care method with intermittent incubator care (asymp-sign (2-tailed) is 0.444. Thus p value 0,05). Intermittent kangaroo care method once daily for three days yet provide maximum results in increased body weight LBW. It is recommended that the implementation of kangaroo care method more often intermittent done every day in order to deliver maximum results yag.